2012
DOI: 10.1002/icd.1748
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Website Claims about the Benefits of Teaching Sign Language to Infants and Toddlers with Normal Hearing

Abstract: The development of proficient communication skills in infants and toddlers is an important component to child development. A popular trend gaining national media attention is teaching sign language to babies with normal hearing whose parents also have normal hearing. Thirty-three websites were identified that advocate sign language for hearing children as a way of promoting better developmental outcomes. These sites make several claims about the positive benefits of teaching hearing infants and toddlers to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…http://www.babysigns.com), despite a growing body of research suggesting that babysign has no effect on children's vocabulary growth (e.g. Johnston, Durieux-Smith & Bloom, 2005;Doherty-Sneddon, 2008;Nelson, White and Grewe, 2012). In line with earlier research, we found no relationship between children's receptive or expressive vocabulary and either the choice of activity or maternal mind-mindedness.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…http://www.babysigns.com), despite a growing body of research suggesting that babysign has no effect on children's vocabulary growth (e.g. Johnston, Durieux-Smith & Bloom, 2005;Doherty-Sneddon, 2008;Nelson, White and Grewe, 2012). In line with earlier research, we found no relationship between children's receptive or expressive vocabulary and either the choice of activity or maternal mind-mindedness.…”
Section: Discussionsupporting
confidence: 82%
“…http:// http://www.tinytalk.co.uk). While there is some debate about the veracity of these claims (see Nelson, White and Grewe, 2012), it has been suggested that the use of babysign encourages more responsive and sensitive caregiving (Vallatton, 2009, and Kirk, Howlett, Pine, and Fletcher, 2013. Meins, Fernyhough, de Rosnay, Arnott, Leekam, and Turner, (2012) argue that mindmindedness (the caregiver's proclivity for treating the child as an intentional being with a mind of his/her own) is a robust means of measuring and quantifying a caregiver's sensitivity and responsiveness to the child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Claimed benefits of baby signs include earlier communication of needs and thoughts, increased language and speech development, improved literacy, increased IQ and cognitive skills, reduced frustration, tantrums, and emotional outbursts, increased parentchild bonding, and increased self-esteem, feeling of satisfaction, and accomplishment (Nelson, White, & Grewe, 2012). Pizer, Walters, and Meier (2007) note that baby signing matches parent ideologies that 'value early communication with infants and promote the adaptation of the physical, social, and linguistic environment to their perceived needs'.…”
Section: Baby Signing Trendmentioning
confidence: 95%
“…According to the researchers, the combination of sign with spoken language accelerated the child's expressive vocabulary in both modalities. Nelson et al (2012) have exposed a lack of strong empirical evidence supporting the use of baby signs. This study evaluated the strength of the research cited on baby sign websites.…”
Section: Research On Baby Signsmentioning
confidence: 98%